EFEITOS DO PREÇO RELATIVO SOBRE A ESTRUTURA PRODUTIVA BRASILEIRA (1983-2020) - Stefan Wilson D'Amato (2023)
The present study assesses the direct and indirect effects of relative prices on Brazil's productive structure and bilateral trade. The contribution of this work to the macroeconomic literature is focused on the empirical scope. In addition, a contribution is made to the study area using the UNCOMTRADE database at product level, according to the SITC Rev2 classification for 4 digits. In this thesis, a theoretical framework was elaborated in which it seeks to associate three currents of thought from the economic growth literature, with the aim of understanding the productive dynamics of the Brazilian economy, according to the following approaches: i) growth models with restriction of the Balance of Payments (BPCG); ii) the Kaldorian approach; and iii) new developmentalism. In the suggested specifications for the econometric models, extensions of the growth model a la Thirlwall will be considered for the equations for both exports and imports. The effects on the productive structure will be evaluated based on the classification developed by Lall (2000) by technological intensity. The econometric method used was panel data controlling the fixed effect (FE). The results corroborate the hypothesis raised in the work that the effects on the level of relative prices affect the productive structure, stimulating the sectors in different ways. Thus, its impacts must be analyzed jointly with income dynamics, whether external or domestic.